PENGARUH MODEL PEMBELAJARAN MODIFIED FREE INQUIRY APPROACH TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATERI GERAK HARMONIS SEDERHANA - Julieta Dewantari, - (2023)
This research is motivated by the low critical thinking abilities of high school students. One of the factors contributing to the low critical thinking abilities of students is the inadequate implementation of the learning models during the learning process.The purpose of this study is to analyze the influence of the modified free inquiry approach in learning models on students' critical thinking skills in the topic of simple harmonic motion. The research design used was a one-group pre-test post-test design with a quantitative method. The population of the study consisted of 10th-grade students in one high school in Bandung, with a sample size of 35 students. The sampling technique used was simple random sampling. The instruments used included Lesson Plans, Learning Implementation Sheets, and Critical Thinking Skills Test Sheets. The results of the study indicated a significant difference between the pre-test and post-test scores. Therefore, it can be concluded that there is a significant influence after the students were given the treatment in the form of applying the modified free inquiry learning model. Furthermore, the improvement in students' critical thinking skills was measured by a normalized gain score of 0.6816, which falls into the moderate category. These results indicate that the influence of the modified free inquiry approach has made a significant contribution to enhancing students' critical thinking skills. Additionally, the student questionnaire obtained a percentage score of 93.3% with an excellent category, indicating that the majority of students responded positively to the implementation of the modified free inquiry learning model.